2023
DOI: 10.1001/jamanetworkopen.2022.49950
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing and Precipitating Factors Associated With Delirium

Abstract: ImportanceDespite discrete etiologies leading to delirium, it is treated as a common end point in hospital and in clinical trials, and delirium research may be hampered by the attempt to treat all instances of delirium similarly, leaving delirium management as an unmet need. An individualized approach based on unique patterns of delirium pathophysiology, as reflected in predisposing factors and precipitants, may be necessary, but there exists no accepted method of grouping delirium into distinct etiologic subg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 400 publications
(1,759 reference statements)
3
65
0
1
Order By: Relevance
“…From the demographic perspective, we found that age is associated with increased risk of delirium, as previously shown 27 . However, even though males represent the larger portion of patients undergoing cardiac surgery, our data indicate that females are more likely to experience delirium, differing from the current literature reporting male sex as an inconsistent risk factor for delirium in both cardiac and noncardiac surgeries [28][29][30] .…”
Section: Discussionsupporting
confidence: 82%
“…From the demographic perspective, we found that age is associated with increased risk of delirium, as previously shown 27 . However, even though males represent the larger portion of patients undergoing cardiac surgery, our data indicate that females are more likely to experience delirium, differing from the current literature reporting male sex as an inconsistent risk factor for delirium in both cardiac and noncardiac surgeries [28][29][30] .…”
Section: Discussionsupporting
confidence: 82%
“…Subtype assignment was based on DOS items 10, 11, and 13, an acknowledged procedure (Scheffer et al, 2011). Most previous studies reported similar findings using different assessment tools (Ormseth et al, 2023). From those reports neglecting sex differences, one recent study analyzed the Delirium Motor Subtype Scale (DMSS) and the Delirium Rating Scale R98 (DRS-R98) in a pooled cohort of medical and surgical in-and outpatients (Trzepacz et al, 2018).…”
Section: Sex-associated Subtype Distributionmentioning
confidence: 99%
“…The investigation of sex differences in neuropsychiatric diseases is clinically relevant to tailor individualized patient care but remains, so far, under-recognized (Tierney et al ., 2017). A recently published comprehensive systematic review consisting of 315 studies and data from more than 100 000 patients indicated that the data remain unclear as to whether sex is a predisposing factor regarding the development of delirium and distinct subtypes (Ormseth et al ., 2023). Sex differences in the incidence of delirium have been reported in surgical patients often observing a higher incidence in men (Aldemir et al ., 2001; Shiiba et al ., 2009; Vasilevskis et al ., 2012; Oh et al ., 2016; Wittmann et al ., 2022), although other studies do not support this notion (Oe et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several randomized controlled trials have evaluated the ability of AChEi to prevent or treat delirium [8][9][10][11][12][13]; however, none has tested these medicines in a critically ill population enriched for preexisting central cholinergic deficits, such as those with dementia. Early studies that focused on prevention of delirium prior to an elective operation showed minimal benefit, although these were of varying methodological rigor [8,9,13,14]. Unfortunately, a large trial comparing behavioral management with haloperidol and placebo versus haloperidol and rivastigmine in a general population of critically ill adults was stopped early due to a signal suggesting increased mortality in the rivastigmine group; however, differences in baseline characteristics between the groups call into question whether this would have been borne out in a fully powered trial [11].…”
mentioning
confidence: 99%
“…1). Given the broad range of predisposing factors and precipitants for delirium among critically ill patients [14], careful study population selection, including those with preexisting cognitive impairment or biomarkers of reduced cholinergic signaling, may maximize the potential for detecting a clinically relevant benefit. Designing such a clinical trial would necessitate identifying a population at high risk for developing delirium.…”
mentioning
confidence: 99%